Safety and Feasibility of Esophagectomy Following Combined Immunotherapy and Chemotherapy for Locally Advanced Esophageal Squamous Cell Carcinoma: A Propensity Score Matching Analysis - Hong, Zhi-Nuan; Gao, Lei; Weng, Kai; Huang, Zhixin; Han, Wu; Kang, Mingqiang (Frontiers in Immunology, 2022)
Objectives Combination of neoadjuvant chemotherapy and immunotherapy (nICT) is a novel treatment for locally advanced esophageal cancer. There is concern that nICT may increase operation difficulty, and postoperative morbidity and mortality. This study aimed to compare short-term outcomes among esophagectomy after neoadjuvant chemoradiotherapy(nCRT) and nICT and for locally advanced esophageal squamous cell carcinoma (ESCC). Methods A retrospective analysis of a prospectively maintained database was performed to identify patients (from January 2017 through July2021) who underwent surgery for ESCC following neoadjuvant therapy. A 1:1 propensity score matching (PSM) with a caliper 0.05 was conducted to balance potential bias. Results A 1:1 PSM was conducted based on clinical stage, age, body mass index (BMI) and tumor location, and then 32 comparable pairs were matched. After PSM, age, gender, BMI, American Society of Anesthesiologists (ASA) status, smoking history, clinical stage, tumor location, lymphadenectomy field, pathological stage, anastomotic position, route of gastric conduit, procedure type, and operative approach were comparable between groups. Compared with nICT group (median, 300 min), the operation time was significantly longer in nCRT group (median, 376 min). However, both groups were comparable in intraoperative blood loss, thoracic drainage volume, ICU stay, postoperative hospital stays, hospital cost. Further, 30-day mortality, 30-day readmission, ICU readmission, and major complications were similar in both groups. nCRT group had advantage in pathological response. The pathological complete response (pCR) was 18.8% (6/32) in nICT group and 43.8% (14/32) in nCRT group(P=0.03). The major pathological response (MPR) was 71.9% (23/32) in nCRT group and 34.4% (11/32) in nICT group (P= 0.03). Conclusions Based on our preliminary experience, esophagectomy appears to be safe and feasible following combined neoadjuvant immunotherapy with chemotherapy for locally advanced esophageal cancer.